Heat Treatment and Changes in Siliceous Rock Quality in the Southern End of the Deseado Massif (Patagonia, Argentina). (2nd October 2021) - Vetrisano, Lucas; Franco, Nora Viviana
ABSTRACT: The use of high-quality rocks and heat-treatment by hunter-gatherers during the initial exploration of America has been emphasized by different authors. Here we present the case of the Southern End of the Deseado Massif (Patagonia, Argentina), where human occupations have been dated from the Pleistocene-Holocene transition until historical times. An intense survey of lithic resources has shown the presence of primary and secondary sources of high quality siliceous rocks, most of them of hydrothermal origin. These siliceous rocks have a highly localized occurrence. In most cases, their quality does not match the one found at the archaeological record, which encompasses caches of artifacts, logistic and multiple activity sites. We present the results of heat treatment experiments on samples from local primary sources. Results obtained are compared with the artifacts found, in order to evaluate the potential utilization of the sources and the presence of heat treatment in the archaeological record.